Effect of Shift Work on the Development of Metabolic Syndrome After 3 Years in Japanese Male Workers - Kawada, Tomoyuki; Otsuka, Toshiaki (Archives of environmental & occupational health, 2014)
A 3-year follow-up study of an occupational cohort was conducted to clarify the effect of the type of shift work on the risk of development of metabolic syndrome (MetS). The subjects were 1,677 Japanese male employees aged 36 to 57. Age, each component of MetS, serum uric acid, serum insulin, lifestyle factors, and occupational position were used for the analyses. The odds ratios (95% confidence intervals) of 2-shift work (n = 686) and 3-shift work (n = 99) against daytime work (n = 868) for the development of MetS, as defined by the National Cholesterol Education Program, were 1.43 (1.05, 1.95) and 0.72 (0.37, 1.41), respectively. When Japanese criteria were adopted for defining MetS, the corresponding odds ratios (95% confidence intervals) were 1.88 (1.29, 2.74) and 0.87 (0.39, 1.97), respectively. The results of the analyses suggested that 2-shift work was a risk factor for the development of metabolic syndrome.